Implementasi Pelaksanaan Zona Integritas pada Fakultas Ilmu Sosial dan Ilmu Politik Universitas Negeri Semarang - Natal Kristiono; Rudi Salam; Hanik Latifah; Indri Astuti; Amalia Adya Prastiwi; Sa’ya Rosada Al Firdaus; Meike Dwi Novita (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2023)
The phenomenon of corruption that occurs in the public sector is not only small scale, but also occurs in public management at the operational level up to that carried out by officials. One effort to prevent corruption is bureaucratic reform, which is implemented by every government agency, including the Faculty of Social Sciences, Semarang State University through the construction of integrity zones. Based on the background above, the author formulates several problems, namely the implementation of building an integrity zone in the context of preventing corruption at the Faculty of Social Sciences, Semarang State University, as well as obstacles in implementing the construction of an integrity zone in the context of preventing corruption at the Faculty of Social Sciences, Semarang State University and their solutions. The research method used is a qualitative approach, with analytical descriptive research specifications. The data used in this research are primary data and secondary data obtained through interviews and literature study, then analyzed qualitatively. The targeted output is journal articles indexed by Sinta.